An Administrative Cluster-based Cooperative Caching (ACCC) strategy for Mobile Ad Hoc Networks. (July 2016) - El Khawaga, Sally E.; Saleh, Ahmed I.; Ali, Hesham A.
Abstract: Recent explosive growth in computing and wireless communication technologies has led to an increasing interest in mobile ad hoc networks (MANET). Among the many challenges for MANET designers and users, data availability is a critical issue. Caching is considered as an effective solution for the availability problem. Although cooperative caching improves the data access by reducing access latency and bandwidth usage in MANETs, it still suffers from several hurdles and technical problems. This paper introduces a new cooperative caching strategy for MANETs, which is called Administrative Cluster-Based Cooperative Caching (ACCC). ACCC keeps at most two copies of the cached data items in each cluster. Moreover, it develops a new administrative module, which perfectly controls the caching process. ACCC is a cluster-based caching strategy, hence, it divides the network into a set of overlapping clusters. Each cluster is managed by a Cluster Manager (CM) as well as a Cluster Backup (CB). ACCC has several salient features that other techniques do not have such as: (i) the integration between CM and CB besides the integration among all the caching modules improves the data availability within the cluster, (ii) ACCC; maximizes the caching hit ratio, reduces access delay, and saves the battery power of network nodes. ACCC is simulated using Java Caching System JCS2 with the efficient platform Java Enterprise Edition EE8 using a client/server model. Experimental results have shown that ACCC outperforms recent cluster-based caching strategies as it introduces higher cache hit ratio as well as better data availability.